Studying the development of young children from two domains: action and symbolic understanding - Jauck, Eva (2019)
This paper aims to illustrate a novel approach to the study of cognitive development by researching two domains of knowledge that have remained separated: action understanding and symbolic understanding of images. First, we show recent research on young children’s action understanding through live actions and actions in images. Then, we address young children’s early symbolic understanding of images in general and digital images displayed in a tablet. Finally, we present some studies that have linked both paths by analyzing the symbolic understanding of images that represent real actions in children aged 2 or older.